Health Systems, Aging, and Inequity: An Example from Chile - Villalobos-Dintrans, P (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Background: Just like many other countries around the world, Chile is facing the challenges of demographic transition and population aging. Considering this context, the question of how prepared the health system is to deal with these challenges arises; Methods: A framework to assess the health system’s preparedness for aging was proposed, considering the health system’s goals and features and using an equity approach. Indicators related to the health system’s goals were calculated for the year 2015 using three nationally-representative sources: health status (suicide rate), financial protection (out-of-pocket and catastrophic expenditures), and responsiveness (satisfaction). Age ratios were used to compare the system’s response to different age groups; Results: Results for Chile revealed the existence of inequities, particularly when assessing the system in terms of its ability to improve health status and financial protection. These gaps increase with age, suggesting that the Chilean health system is not prepared to meet older people’s needs; and Conclusions: These results call for a reform in the health system, as well as the need for implementing a long-term care system in the country. © 2020 by the author. Licensee MDPI, Basel, Switzerland.